CORRELATION BETWEEN SENIORITY AND VERBAL ABUSE AMONG TEENAGE GAMERS - Suryani Madaniyah; Hetty Murdiyani; Fety Khosianah (P3I UMSurabaya, 2024)
This study investigates the relationship between seniority and verbal abuse among teenage gamers who play in group settings. Using a quantitative correlational approach, data were collected from 61 respondents through purposive sampling. A Likert-scale questionnaire was employed to measure both seniority and verbal abuse. The results of Pearson’s correlation analysis indicated a significance level of 0.772 (p > 0.05) with a correlation coefficient of -0.038, suggesting no significant relationship between seniority and verbal abuse among the participants. This research provides insights into the dynamics of hierarchy and communication patterns within gaming communities.